Review Article: Methods Of Preparation And Ointment Bases Used In Ointment Preparations - Ayu Mahdiati; Hasanah Alifah Marsya; Marvina; Nabila Okdania; Elpa Giovana Zola (CV. AFDIFAL MAJU BERKAH, 2026)
Ointments, semi-solid topical preparations, are increasingly being developed with natural ingredients for wound healing and antibacterial effects amidst the challenges of antibiotic resistance in Indonesia. This study reviews herbal ointment formulations based on extraction techniques, manufacturing methods, bases, physical quality, and biological effectiveness. Using a descriptive qualitative literature study with narrative synthesis from national journals (2020-2025). The population was all related articles; a purposive sample of 40 articles based on completeness and quality. Instruments were scientific documents; thematic and descriptive clustering analysis. The results showed that ethanol extraction produced flavonoids and tannins; the melting/trituration method with a hydrocarbon/PEG base met standards (pH 4.5-7, spreadability 5-7 cm, adhesiveness >4 seconds), with antibacterial activity against Staphylococcus aureus. In conclusion, herbal ointments have the potential to be safe phytopharmaceuticals, requiring clinical validation.